Edible cannabis - Zipursky, Jonathan S.; Stall, Nathan M.; Bogler, Orly D. (Canadian Medical Association journal (CMAJ), 2020)
In this article, five things to know about edible cannabis are presented. These are the following: 1. More than 40% of North American nonmedical cannabis users consume edibles. 2. Edibles have a long latency period and duration of action. 3. Unfamiliarity with edible dosing and difficulties in dividing edibles can result in unintentional overdose. 4. Psychiatric and cardiovascular complications are more likely with edibles. 5. Unintentional exposure to edibles is particularly dangerous for children.